Effects of graded carbohydrate supplementation on the immune response in cycling - Scharhag, J.; Meyer, T.; Auracher, M.; Gabriel, H. H.; Kindermann, W. (Medicine & Science in Sports & Exercise, 2006)
Purpose: This study examined the acute immune response after three standardized cycling sessions of 4-h duration in the field with varying carbohydrate (CHO) supplementation in a randomized, double-blind, placebo-controlled fashion. We hypothesized that the ingestion of carbohydrate (6 or 12% CHO beverages; placebo (P) without CHO) during exercise attenuates the exercise-induced immune response in a dose-dependent manner.